2018
DOI: 10.1080/09658211.2018.1502322
|View full text |Cite
|
Sign up to set email alerts
|

Selective effects of specificity inductions on episodic details: evidence for an event construction account

Abstract: Prior research has suggested that an episodic specificity induction - brief training in recollecting the details of a past event - affects downstream performance on remembering past and imagining future events, solving problems, and thinking creatively. We have hypothesised that a process common to these tasks that the induction may target is event construction - assembling and maintaining a mental scenario filled with details related to settings, people, and actions. We test this hypothesis by having particip… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

12
53
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(67 citation statements)
references
References 56 publications
12
53
2
Order By: Relevance
“…However, they focus more on the practical aspects and applications of utilising EFT, rather than particular training in improving this type of cognitive ability. A series of studies utilising a laboratory-based paradigm of a brief video followed by an interview about details of the video can increase episodic detail for future events, which generalises to improved performance on tasks which follow this induction (Madore et al, 2014a(Madore et al, , 2014b(Madore et al, , 2015(Madore et al, , 2016(Madore et al, , 2019. These studies demonstrate the important role of episodic detail on a range of tasks; however, the ability to generate higher numbers of specific events is not typically tested, rather, details are assessed within specific events.…”
mentioning
confidence: 99%
“…However, they focus more on the practical aspects and applications of utilising EFT, rather than particular training in improving this type of cognitive ability. A series of studies utilising a laboratory-based paradigm of a brief video followed by an interview about details of the video can increase episodic detail for future events, which generalises to improved performance on tasks which follow this induction (Madore et al, 2014a(Madore et al, , 2014b(Madore et al, , 2015(Madore et al, , 2016(Madore et al, , 2019. These studies demonstrate the important role of episodic detail on a range of tasks; however, the ability to generate higher numbers of specific events is not typically tested, rather, details are assessed within specific events.…”
mentioning
confidence: 99%
“…A first way to show that the effect of the retrieval-orientation manipulation is episodic-specific is to include a task that does not rely on episodic memory mechanisms. For instance, some studies using specificity inductions also included a description task in their design (Madore et al, 2014;Madore, Jing, & Schacter, 2019b;Madore & Schacter, 2016). They found an increase in the number of reported episodic details when remembering the past or imagining the future after the specificity induction while the induction did not impact the number of reported details in the description task.…”
Section: Discussionmentioning
confidence: 99%
“…Effortful simulations of future events can increase their vividness (Boland, Riggs, & Anderson, 2018;Madore, Jing, & Schacter, 2018), and the plausibility of them occurring in one's life (Boland et al, 2018;Gregory, Cialdini, & Carpenter, 1982;Szpunar & Schacter, 2013). Indeed, episodic future thinking can increase the availability of information about future experiences with which to make decisions and form intentions (Altgassen et al, 2015;Tversky & Kahnemann, 1974).…”
mentioning
confidence: 99%
“…On a related note, research has shown that recalling past experiences can prime an episodic thinking style, and subsequently increase detail/vividness when thinking of future events (e.g., Madore, Jing, & Schacter, 2018;Madore & Schacter, 2014;. This is thought to be because mentally simulating past and future events involves a similar process of generating and maintaining a mental scene populated with details (Madore et al, 2018). Indeed, activating an episodic thinking style, whether through past or future thinking, increases detail in future thinking (Madore et al, 2018).…”
mentioning
confidence: 99%
See 1 more Smart Citation